Barium strontium titanate nanocrystalline thin films prepared by soft chemical method - Mazon, T.; Zaghete, M. A.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Barium strontium titanate (Ba0.65Sr0.35TiO3) nanocrystalline thin films, which were produced by the soft chemical method, were crystallized at low temperature using a domestic microwave oven. A SiC susceptor were used to absorb the microwave energy and rapidly transfer the heat to the film. Low microwave power and short time have been used. The films obtained are crack-free, well-adhered, and fully crystallized. The microstructure displayed a polycrystalline nature with nanograin size. The metal-BST-metal structure of the thin films treated at 700 degrees C show food electric properties. The ferroelectric nature of the BST35 thin film was indicated by buttertly- shaped C-V curves. The capacitance-frequency curves reveal that the dielectric constant may reach a value up to 800 at 100kHz. The dissipation factor was 0.01 at 100kHz. The charge storage density as function of applied voltage graph showed that the charge storage densities are suitable for use in trench type 64 Mb ( 1-5 mu C/cm(2) and 265 Mb (2-11 mu C/cm(2)) DRAMs. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: BST; films; microwave processing; dielectric properties; capacitors